2022
DOI: 10.1007/s12671-022-01960-1
|View full text |Cite
|
Sign up to set email alerts
|

Economic Evaluations of Mindfulness-Based Interventions: a Systematic Review

Abstract: Objectives This study includes a systematic review of cost-effectiveness analyses (CEAs) and cost–benefit analyses (CBAs) of mindfulness-based interventions (MBIs). Methods A literature search was conducted using PubMed, Web of Science, JSTOR, and CINAHL for studies published between January 1985 and September 2021, including an original cost-related evaluation of an MBI. A qualitative assessment of bias was performed using the Drummond checklist. Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 83 publications
0
10
0
Order By: Relevance
“…Previous studies have examined MBSR cost-effectiveness (e.g., D’Amico et al, 2024 ; Feliu-Soler et al, 2018 ; Herman et al, 2017 ; Knight et al, 2015 ; Lengacher et al, 2015 ; Perez-Aranda et al, 2019 ), but methodological quality of these studies has been variable. A recent systematic review provides promising evidence that MBSR is cost-effective across nine countries, including the United States, even reducing costs to both payers and society (Zhang et al, 2022 ). There are impactful opportunities to replicate and extend cost-effectiveness findings on MBSR.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have examined MBSR cost-effectiveness (e.g., D’Amico et al, 2024 ; Feliu-Soler et al, 2018 ; Herman et al, 2017 ; Knight et al, 2015 ; Lengacher et al, 2015 ; Perez-Aranda et al, 2019 ), but methodological quality of these studies has been variable. A recent systematic review provides promising evidence that MBSR is cost-effective across nine countries, including the United States, even reducing costs to both payers and society (Zhang et al, 2022 ). There are impactful opportunities to replicate and extend cost-effectiveness findings on MBSR.…”
Section: Discussionmentioning
confidence: 99%
“…Yoga/mindfulness interventions may also be cost effective, an important consideration that influences implementation. 72 Community buy-in and family engagement paired with PA and/or nutrition interventions can be influential in promoting a healthy lifestyle and a positive SEC. 73 Implementing activity-friendly supports, such as playground greening and addition of community parks, are ways a community may update their physical environment to promote PA during, before and after school hours.…”
Section: Implications For School Health Policy Practice and Equitymentioning
confidence: 99%
“…Implementing mindfulness curriculum, engaging families and communities, and greening of the playground may be techniques districts and schools can use to nurture the SEC 71 and promote PA and healthy dietary behaviors. Yoga/mindfulness interventions may also be cost effective, an important consideration that influences implementation 72 …”
Section: Implications For School Health Policy Practice and Equitymentioning
confidence: 99%
“…Other reviews, for example, examining impact of CBT and mindfulness on sleep disturbances in survivors of cancer, have found both CBT and mindfulness for insomnia to be effective [ 30 ], although with CBT often being pointed to as having the strongest effect and the findings for MBIs being somewhat more inconsistent [ 28 ]. There are however studies pointing to MBIs as effective in coping with chronic health disorders including cancer [ 11 , 12 , 31 ], and a recent systematic review found mindfulness-based stress reduction interventions to be less costly and more effective when compared with the usual care of CBT among patients with health challenges including breast cancer [ 32 ].…”
Section: Introductionmentioning
confidence: 99%